Meningkatkan Minat Belajar Bahasa Inggris Dengan Aplikasi Duolingo Sebagai Media Interaktif di Rumah Pintar YAFSI - Sasmitha, Ikhwa; Thamrin, Husni (Pengelola Jurnal Politeknik Negeri Ketapang Jl. Rangga Sentap, Dalong Sukaharja, Ketapang 78813. Telp. (0534) 3030686 Kalimantan Barat, 2022)
In the era of globalization, children are required to be able to learn the language of other countries in order to become their guide in exploring a world full of fierce competition from various directions in obtaining the necessities of life such as work, education, and so on. The language that is most recommended to be mastered is English, because English has been designated as a universal language that is commonly used to interact with people around the world. This activity was carried out with a comprehensive mentoring method for Rupin Yafsi's children through socializing the importance of using English in the era of globalization, using the Duolingo application, and testing out the learning achievements obtained after using the Duolingo application. The Intervention Program used in this practicum is the Mezzo Intervention by Zastrow which consists of; Preparation (with a Non-Directive Approach), Intake / Engagement, Assessment, Planning, Implementation and Action Plan, Evaluation and Termination. The final output achieved from this activity is the increase in the digital literacy skills of Rupin Yafsi's children in utilizing digital learning applications that are very useful to increase their new knowledge and insights